Caring for relations and organizational success—conceptualization of an Augustinian leadership scale - Slob, Henri; van Geest, Paul; Commandeur, Harry (Frontiers in Psychology, 2023)
While making great strides in recent decades to connect leadership and human flourishing, the positive leadership literature has yet to focus on the aspect of the communal. Based on a close reading of Augustine’s works, this paper examines Augustinian leadership and emphasizes the importance of a view on leadership that aims at community building and contains an ethical framework characterized by veracity. This leadership style is founded on caritas (Gr.: agape, Eng.: love) as the main motive for leaders. Based on Augustine’s thinking, this kind of love is defined as a way to attain knowledge. We identify four subconstructs to constitute an Augustinian leadership scale: Centrality of the community, Veracity, Empathy and Success (through temperance). We provide theoretical grounds for the distinctiveness of this leadership construct as compared with neighboring constructs. Finally, we propose a testable framework of Augustinian leadership with a direct effect on affective commitment as well as a mediated effect, and with a sense of belonging as the mediating variable. We provide ideas for future research and present practical implications of the theoretical insights on Augustinian leadership.